The Influence of Competency, Job Achievement and Job Loyalty On Employee Performance of PT Inti Vulkatama - Kevin Setiawan; Salfadri Salfadri; Delvianti Delvianti (Fakultas Ekonomi, Universitas Ekasakti, 2025)
The aim of this research is to find out: Which indicators are the most dominant in the variables of competence, work performance, work loyalty and employee performance; The influence of competency on employee performance; The influence of work performance on employee performance; The influence of work loyalty on employee performance; The influence of competence, work performance and work loyalty on the performance of PT Inti Vulkatama Padang employees. This type of research uses quantitative research in this research. The population in this study were all employees of PT Inti Vulkatama Padang with a total of 55 samples, using a total sampling technique. Data collection uses primary data. The analytical methods for this research are descriptive analysis, multiple linear regression analysis, coefficient of determination, and hypothesis testing with the t-test and F-test. Research results: The dominant indicator of the competency variable is integrity with a value of 4.49 or TCR 89.72%, for work performance it is time with a value of 4.36 or TCR 87.20% and for work loyalty it is interpersonal relationships with a value of 4. 53 or TCR 90.70%, while employee performance is work behavior with a value of 4.44 or TCR 88.60%; Competency has a positive and insignificant effect on employee performance; Job performance has a positive and significant effect on employee performance; Work loyalty has a positive and insignificant effect on employee performance; Competence, work performance and work loyalty simultaneously have a positive and significant effect on the performance of PT Inti Vulkatama Padang employees. The contribution of competence, work performance and work loyalty to the performance of PT Inti Vulkatama Padang employees is 29.80% while the remaining 70.20% is influenced by other variables outside this research.